APPLICATION OF COOPERATIVE LEARNING TYPE MAKE A MATCH MODEL TO INCREASE ACTIVITY AND LEARNING STUDENTS IN MATHEMATICS LEARNING (Classroom Action Research in Class IV.C Bengkulu City Elementary School 1) - Hidayat, Cucu; Puspita, Hilda (UNIB Press, 2017)
Abstract: This study aimed to increase the activity and learning outcomes of mathematics by applying Make A Match Model in class IV C SDN 1 Kota Bengkulu. The subjects of this study amounted to 30 students. Data collection techniques used were observation, interview, and documentation. The data collected in this study were observational data of student and teacher activities in mathematics learning and matehematics test results. Data analysis techniques used descriptive statistical analysis and quantitative analysis. The results of this study indicate an increase in students activites and learning outcomes in mathematics learning. This was show from cycle 1, II and III. The ss’activities has increased compared to the pre-cycle. The results students activities meet the criteria for success of action, name ly the success of the learning process by students is said to be good, if every aspect of theobservation sheet students all come up with information that has been carried out well and the average value of students is ? 70 and increases each cycle so that classical learning completeness is achieved that is 75%.. Thus, the application of the learning model Make a Match can increase the student activity and learning outcomes in mathematics learning in grade IV C of SDN 1 Kota Bengkulu.Keywords: Make a Match, Activities and student learning outcomes, mathematics learning